An azobenzene-based photoswitchable crystal growth modifier - Nealon, Gareth; Brown, David; Jones, Franca; Parkinson, Gordon; Ogden, Mark (The Royal Society of Chemistry, 2017)
An aspartic acid functionalised azobenzene derivative is found to be a light-switchable crystal growth modifier of calcite. UV irradiation of the molecule reversibly switches it to the cis isomer, which is a significantly less effective crystal growth inhibitor than the trans isomer. Visible light, or heat switches the inhibitor back “on”. Extended irradiation degrades the inhibitor such that it is irreversibly switched “off”. It was shown that the trans isomer is preferentially absorbed on to the crystal surface, which is consistent with its greater efficacy as an inhibitor.